2020
DOI: 10.3390/su12177118
|View full text |Cite
|
Sign up to set email alerts
|

Green Marketing as a Part of the Socially Responsible Brand’s Communication from the Aspect of Generational Stratification

Abstract: Green marketing is focused on a responsible approach to the environment, which is integrated into various areas of society. In order to build a successful and socially responsible brand, it strives to apply environmental principles that attract new customers or strengthen the loyalty of existing ones. To ensure success, it is necessary to focus on green marketing as a part of socially responsible brands’ communication to individual target groups, which can be divided according to the age of the consumer genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
1
19
0
3
Order By: Relevance
“…Historically, the term green marketing has evolved from its early concepts which has been divided into three different eras with different changing characteristics. There are several important differences between the first era, known as ecological green marketing, followed by the second and third era named green environmental marketing and as a sustainable green marketing respectively (Nadanyiova, Gajanova & Majerova, 2020 understanding the similarities and differences between these earliest concepts, the development of green marketing can be further appreciated. The ecological green marketing era was initially formulated in the early 1960s to 1970s, to which attention towards pollution was given much thought.…”
Section: Green Marketingmentioning
confidence: 99%
“…Historically, the term green marketing has evolved from its early concepts which has been divided into three different eras with different changing characteristics. There are several important differences between the first era, known as ecological green marketing, followed by the second and third era named green environmental marketing and as a sustainable green marketing respectively (Nadanyiova, Gajanova & Majerova, 2020 understanding the similarities and differences between these earliest concepts, the development of green marketing can be further appreciated. The ecological green marketing era was initially formulated in the early 1960s to 1970s, to which attention towards pollution was given much thought.…”
Section: Green Marketingmentioning
confidence: 99%
“…From a wide search, bibliometric studies were found that related CSR with communication (e.g., [9,10]) and marketing with socially responsible brand communication [11]. Ji et al's [9] study assesses how CSR communication research has developed over the past four decades and the results demonstrate that CSR communication is a maturing area of research.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The company is increasingly focused on environmental protection, local community development, ethical business and improving relationships with employees and partners. [6,7] This process also includes the issue of the circular economy, the aim of which is to use as few resources as possible through more efficient procedures, elimination of waste generation, reuse, processing and recycling. [8][9][10][11][12][13][14] It focuses mainly on material cycles and uses energy from renewable sources.…”
Section: Introductionmentioning
confidence: 99%